Code Mixing as an Indicator for Culinary Expertise and Identity Construction in MasterChef Indonesia - Safira, Azzahra Fatimah Syafa; Farida, Alief Noor (Universitas Pahlawan Tuanku Tambusai, 2025)
A lot of research has been done on code mixing, which frequently happens in multilingual communities, especially on its variations, causes, and goals. Research on code mixing techniques in professional mass media and their connection to identity formation is still lacking, though. By analyzing code mixing in the television program MasterChef Indonesia and concentrating on how it denotes culinary proficiency and shape’s identity, this study closes that gap. 20 utterances from several video during seasons 10–12 MasterChef Indonesia are examined in this study. Using a descriptive qualitative methodology and analyzed through analytical approach by using several theories from Muysken (2000), Hoffman (1991), and Bucholtz Hall (2005). According to the study's findings, insertion is the most prevalent kind of code mixing and is employed to express ideas, feelings, and culinary phrases. It also aids in the development of identities, such as those of experts, mentors, or students.